Imaging observation of intervertebral disc degeneration in patients with old thoracolumbar fracture-related kyphotic deformity - Xi-long Cui; Ao Ding; Wen Yin; Wan-mei Yang; Wei Zhang; Hao Wu; Ji-shi Jiang; Yun-lei Zhai; Zi-kai Hua; Hai-yang Yu (Scientific Reports)
Abstract Old thoracolumbar fracture with kyphosis (OTLFK) often results in low back pain, with intervertebral disc degeneration being a significant contributor. We hypothesized that patients with OTLFK exhibit distinct patterns of disc degeneration compared to those with chronic low back pain without kyphotic deformity. This study aimed to investigate the characteristics of disc degeneration in OTLFK patients and explore its association with sagittal spinal parameters and endplate injury. A retrospective analysis was conducted on 52 patients with OTLFK (observation group, OG) and 104 age-, gender-, and BMI-matched patients with chronic low back pain (control group, CG) treated at our hospital between February 2017 and March 2023. Intervertebral disc degeneration from T11/12 to L5/S1 was assessed using MRI T2-weighted images and the Pfirrmann grading system. Sagittal spinal parameters—including lumbar lordosis (LL), thoracic kyphosis (TK), local kyphosis Cobb angle (LKCA), thoracolumbar kyphosis (TLK), pelvic tilt(PT), sacral slope(SS), and sagittal vertical axis (SVA)—and endplate injury grades were measured in the OG. Differences in disc degeneration between the two groups were compared, and correlations between disc degeneration, sagittal parameters, and endplate injury were analyzed. The OG exhibited significantly higher overall disc degeneration grades compared to the CG (p < 0.05), particularly at levels T11/12, T12/L1, L1/2, and L2/3. In the OG, grade IV and V degenerations were predominantly found from T11/12 to L2/3, whereas in the CG, they were mainly at L4/5 and L5/S1. Disc degeneration in the OG was significantly correlated with sagittal parameters and endplate injury grades (p < 0.05). Patients with OTLFK have higher grades of disc degeneration in the thoracolumbar region compared to those with chronic low back pain without kyphosis. Disc degeneration in OTLFK is associated with abnormal sagittal alignment and endplate injury, suggesting that kyphotic deformity and altered spinal biomechanics contribute to accelerated disc degeneration.